Multi-Objective Optimization of a Spoke Type Synchronous Machine With Ferrite Magnets Considering Torque Ripple and Demagnetization - Marcelo D. Silva; Sandra Eriksson (IEEE Access, 2025)
Electric machines are used in various environments with noise and vibration requirements. Torque ripple is a key design parameter that is considered when evaluating these. While rotor skewing is a common practice for reducing torque ripple in induction machines (IM), strategies for permanent magnet synchronous machines (PMSM) still vary significantly. This paper enhances a Spoke-Type PMSM that utilizes ferrite permanent magnets (PMs). It focuses on torque ripple at maximum torque at base speed, maximum torque, and the risk of permanent demagnetization. The study investigates torque ripple reduction by exploring rotor surface geometric parameters, allowing for the examination of a wide range of rotor surface configurations. The study is developed using experimentally validated FEM models. Furthermore, the study shows that, for Spoke Type PMSM with ferrite PMs, the inclusion of demagnetization in the optimization process alters the optimal design by skewing the Pareto front toward low-performing solutions. Instead, including a performance metric that represents the demagnetizing effects of a fault is sufficient to achieve a high-performing design with resilience towards demagnetization. Additionally, the results also show that the Spoke Type PMSM with ferrite PMs has another advantage apart from being rare-earth free; it can be designed to have minimal torque ripple without significant performance degradation.